Towards a Sustainable Future: Promoting Sustainability, Sustainability Accounting and Reporting among Future Professional Accountants - Arnold V. Salcedo; Shane S. Salcedo, CPA (Center for Risk Management & Sustainability and RSF Press, 2021)
While most of the sustainability studies focused are on areas of engineering and architecture, sustainability accounting and reporting are concepts that need to be introduced among people nowadays, specifically accountancy students, with the belief that the students today, will become the workforce and leaders of tomorrow. The study focused on promoting the various concepts among ninety-six (n=96) accountancy students who are in their terminal year. The students were subjected to a pre-test & post-test experimental design group with viewing video presentations on triple bottom-line, sustainability reporting, true cost accounting and a sample of Global Reporting Initiative Report (GRI) as intervention activities, that aimed to provide an overview and a level of understanding on the targeted concepts. Results show a significant difference on the level of awareness before and after the three concepts were introduced. The participants were willing to learn more about sustainability accounting while half of them would consider to enroll in a graduate program that specializes on leadership in a sustainable enterprise along with management courses concentrating on sustainability. As a conclusion, sustainability accounting and reporting in the Philippines, still has a long way to go and currently at its infancy stage before becoming a distinguished program or a course that will be embedded in the academic curricula or be fully recognized by businesses and industries from both national and local levels. The study can be further enhanced to include the level of commitment and motivation of students to such concepts.